Adsorption of congo red onto wetting-drying silica A-300 and its mixture with hydrophobic silica AM1-300 - Klymenko, N.Yu.; Krupska, T.V.; Turov, V.V. (Reports of the National Academy of Sciences of Ukraine, 2023)
This study investigates the pH-dependency of the adsorption of congo red anionic dye from an aqueous solution onto the surface of wetting-drying hydrophilic silica A-300 with different bulk densities and composite A-300/ AM1-300. It was found that the maximum dye adsorption onto the samples studied was observed in an acid solution (pH 3.5) as a result of the electrostatic attraction of dye molecules to the sample surface. With an increase of pH to 8.5, a significant decrease in the adsorption of congo red was observed due to the competition of hydroxyl ions with dye anionic groups for adsorption centres on the silica surface. It is shown that a composite system based on a mixture of hydrophilic and hydrophobic silica has a high adsorption capacity in relation to an anionic dye in a wide range of the solution pH. At pH 5.5, the adsorptive capacity of the A-300/AM1-300 composite system is 3.6 and 5.7 times higher as compared to A-300 silica with a bulk density 300 and 175 g/L, respectively. At pH 8.5, the ultimate adsorption of the A-300/AM1-300 composite is 2 and 6.6 times higher than that of A-300 with a bulk density 175 and 300 g/L, respectively.